Developmental timing differences underlie armor loss across threespine stickleback populations. Issue 6 (8th November 2017) - Currey, Mark C.; Bassham, Susan; Perry, Stephen; Cresko, William A.
Abstract : Comparing ontogenetic patterns within a well‐described evolutionary context aids in inferring mechanisms of change, including heterochronies or deletion of developmental pathways. Because selection acts on phenotypes throughout ontogeny, any within‐taxon developmental variation has implications for evolvability. We compare ontogenetic order and timing of locomotion and defensive traits in three populations of threespine stickleback that have evolutionarily divergent adult forms. This analysis adds to the growing understanding of developmental genetic mechanisms of adaptive change in this evolutionary model species by delineating when chondrogenesis and osteogenesis in two derived populations begin to deviate from the developmental pattern in their immediate ancestors. We found that differences in adult defensive morphologies arise through abolished or delayed initiation of these traits rather than via an overall heterochronic shift, that intra‐population ontogenetic variation is increased for some derived traits, and that altered armor developmental timing differentiates the derived populations from each other despite parallels in adult lateral plate armor phenotypes. We found that changes in ossified elements of the pelvic armor are linked to delayed and incomplete development of an early‐forming pelvic cartilage, and that this disruption likely presages the variable pelvic vestiges documented in many derived populations.